If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(8 + -3x) = 4x + -9 (8 * 2 + -3x * 2) = 4x + -9 (16 + -6x) = 4x + -9 Reorder the terms: 16 + -6x = -9 + 4x Solving 16 + -6x = -9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 16 + -6x + -4x = -9 + 4x + -4x Combine like terms: -6x + -4x = -10x 16 + -10x = -9 + 4x + -4x Combine like terms: 4x + -4x = 0 16 + -10x = -9 + 0 16 + -10x = -9 Add '-16' to each side of the equation. 16 + -16 + -10x = -9 + -16 Combine like terms: 16 + -16 = 0 0 + -10x = -9 + -16 -10x = -9 + -16 Combine like terms: -9 + -16 = -25 -10x = -25 Divide each side by '-10'. x = 2.5 Simplifying x = 2.5
| 2d-11=3 | | -3(x-7)-18= | | 10log(x/10^-12)=150 | | -3(x-6)+12= | | 14-3g=8 | | 72=(2x+4)*9 | | 5n^2=2n | | 5(c+4c)= | | n+0=6 | | y^2-4y+12x-8=0 | | 3s-3=3 | | 2(8-3)=4x-9 | | 10=12-2f | | -3(6-2x)=4(8+4) | | 2y-6+xy-3x= | | -3(6-2x)=4(8+5) | | 4z+10=18 | | ln(2x-99)=0 | | (x-y)x/y=y/x-y(x-y) | | 3.14(5)2(8)= | | X+SqrtX+3=3 | | 8cos(3x)-4*(sqrt(3))=0 | | 17-x/-2=10 | | 17-x/=10 | | ysquared+y=20 | | u/6=-24 | | f(x)=3x^2+7x-9 | | 8x-7y+92=-11 | | 5×4×6/1/2 | | 8ln(x-5)=12 | | 6x+7y-32=-12 | | 2x^3-6x+6=0 |